Neural Plasticity Induced by Hearing Aid Use - Karawani, Hanin; Jenkins, Kimberly; Anderson, Samira (Frontiers in Aging Neuroscience, 2022)
Age-related hearing loss is one of the most prevalent health conditions in older adults. Although hearing aid technology has advanced dramatically, a large percentage of older adults do not use hearing aids. This untreated hearing loss may accelerate declines in cognitive and neural function and dramatically affect the quality of life. Our previous findings have shown that the use of hearing aids improves cortical and cognitive function and offsets subcortical physiological decline. The current study tested the time course of neural adaptation to hearing aids over the course of six months and aimed to determine whether early measures of cortical processing predict the capacity for neural plasticity. Seventeen (9 females) older adults (mean age = 75 years) with age-related hearing loss with no history of hearing aid use were fit with bilateral hearing aids and tested in six testing sessions. Neural changes were observed as early as two weeks following the initial fitting of hearing aids. Increases in N1 amplitudes were observed as early as two weeks following the hearing aid fitting, whereas changes in P2 amplitudes were not observed until twelve weeks of hearing aid use. The findings suggest that increased audibility through hearing aids may facilitate rapid increases in cortical detection, but a longer time period of exposure to amplified sound may be required to integrate features of the signal and form auditory object representations. The results also showed a relationship between neural responses in earlier sessions and the change predicted after six months of the use of hearing aids. This study demonstrates rapid cortical adaptation to increased auditory input. Knowledge of the time course of neural adaptation may aid audiologists in counseling their patients, especially those who are struggling to adjust to amplification. A future comparison of a control group with no use of hearing aids that undergoes the same testing sessions as the study’s group will validate these findings.